(3TQM bUjOI GdfGHZI GdPHjGfis - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s ((3eMeO Hf CHj GdaVd GdUGFYi GdHjgbi s)
(3ChdgG (B:s
(3jNGWH OGQ gPg GdeQCI HGdecGf GdeQJaY ef GdGQV hGdSfO eG bGHdc ef GQJaGY GdhGOi hGdLHd s
(3BNQgG (B:s
(3Hbhd gPG GdPi PcQJ YPQi aEf de jfaYfi JMjQJ hde GgJO dhLg jNQLfi Yf ZVHc hhYjOc EjGi JeJ GdbUjOI HfaSgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs